Phase II double-blind placebo-controlled randomized study of armodafinil for brain radiation-induced fatigue. Issue 10 (12th May 2015) - Page, Brandi R.; Shaw, Edward G.; Lu, Lingyi; Bryant, David; Grisell, David; Lesser, Glenn J.; Monitto, Drew C.; Naughton, Michelle J.; Rapp, Stephen R.; Savona, Steven R.; Shah, Sunjay; Case, Doug; et al.
Abstract: Background: Common acute-term side effects of brain radiotherapy (RT) include fatigue, drowsiness, decreased physical functioning, and decreased quality of life (QOL). We hypothesized that armodafinil (a wakefulness-promoting drug known to reduce fatigue and increase cognitive function in breast cancer patients receiving chemotherapy) would result in reduced fatigue and sleepiness for patients receiving brain RT. Methods: A phase II, multi-institutional, placebo-controlled randomized trial assessed feasibility of armodafinil 150 mg/day in participants receiving brain RT, from whom we obtained estimates of variability for fatigue, sleepiness, QOL, cognitive function, and treatment effect. Results: From September 20, 2010, to October 20, 2012, 54 participants enrolled with 80% retention and 94% self-reported compliance. There were no grade 4–5 toxicities, and the incidence of grade 2–3 toxicities was similar between treatment arms, the most common of which were anxiety and nausea (15%), headaches (19%), and insomnia (20%). There were no statistically significant differences in end-RT or 4 week post-RT outcomes between armodafinil and placebo in any outcomes (Functional Assessment of Chronic Illness Therapy [FACIT]-Fatigue, Brief Fatigue Inventory, Epworth Sleepiness Scale, FACT-Brain, and FACIT-cognitive function). However, in participants with more baseline fatigue, those treated with armodafinil did better than those who received the placebo on the end-RT assessments for several outcomes. Conclusion: Armodafinil 150 mg/day was well tolerated in primary brain tumor patients undergoing RT with good compliance. While there was no overall significant effect on fatigue, those with greater baseline fatigue experienced improved QOL and reduced fatigue when using armodafinil. These data suggest that a prospective, phase III randomized trial is warranted for patients with greater baseline fatigue.